Оценка энергетических показателей породоразрушающих инструментов в пространственно искривленных скважинах - Гасанов, Р.А.; Ширали, И.Я.; Гасанов, И.З.; Джамалов, В.Р. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
In is being considered work the task of axial loading on to rock destraction bit determination in spatial borehole are set up and solved. With this objective interaction of machine aggregation and its elements with the spatial borehole well walls on it different (protuberant, concave and rectilineal) parts for the various drilling process steps have been studied. Correspoding analytical expressons for evaluation and desigu of realized drilling prosess steps technological parameters. Suggested solutions allow to make decisons for decreasing of rosk destraction power intensity of the spatial borehole drilling process.